ANALISIS PENGARUH KETIDAKPASTIAN LINGKUNGAN TERHADAP HUBUNGAN ANTARA ASIMETRI INFORMASI DAN MANAJEMEN LABA - Fitri Wahyu Risalia; Didik Ardiyanto (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to examine the influence of uncertainty environment to the relationship between information asymmetry and earnings management. The number from board of commissioners and background of audit committee used as control variable. Sample in this study consists of 103 manufacture companies listed in Indonesian Stock Exchange that publish annual report in year 2012. Analysis technique in this study uses multiple analysis regression consists of three regression models to examine the influence of uncertainty environment to the relationship between information asymmetry and earnings management.The empirical result of this study show that information asymmetry have positively significant influenced on earnings management with share price volatility as a measured of information asymmetry. Uncertainty environment as moderating variable measured by complex environment have positive significant on relationship between share price volatility and earnings management while the dynamic environment have significant influenced on relationship between information asymmetry and earnings management.Abstract Berbahasa Inggris.